2000
DOI: 10.1021/jf9904968
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and Phytotransformation of Organophosphorus Pesticides by Axenically Cultivated Aquatic Plants

Abstract: The uptake and phytotransformation of organophosphorus (OP) pesticides (malathion, demeton-S-methyl, and crufomate) was investigated in vitro using the axenically aquatic cultivated plants parrot feather (Myriophyllum aquaticum), duckweed (Spirodela oligorrhiza L.), and elodea (Elodea canadensis). The decay profile of these OP pesticides from the aqueous medium adhered to first-order kinetics. However, extent of decay and rate constants depended on both the physicochemical properties of the OP compounds and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
60
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 120 publications
(67 citation statements)
references
References 24 publications
(28 reference statements)
5
60
1
1
Order By: Relevance
“…Interestingly, the opposite appears to have occurred. For example, whereas Gao et al [23] documented less than a 50% reduction in aqueous malathion concentration over 48 h (nominal concentration applied ¼ 1,000 mg/L), the present study's data suggest much higher dissipation rates, because all of the macrophyte treatments containing Elodea made the water completely non-toxic to Daphnia within 48 h, even at the highest malathion concentrations tested.…”
Section: Discussioncontrasting
confidence: 84%
See 3 more Smart Citations
“…Interestingly, the opposite appears to have occurred. For example, whereas Gao et al [23] documented less than a 50% reduction in aqueous malathion concentration over 48 h (nominal concentration applied ¼ 1,000 mg/L), the present study's data suggest much higher dissipation rates, because all of the macrophyte treatments containing Elodea made the water completely non-toxic to Daphnia within 48 h, even at the highest malathion concentrations tested.…”
Section: Discussioncontrasting
confidence: 84%
“…However, although many highly-lipophilic insecticides with Log K OW values greater than 6.0 (e.g., pyrethroid and organochlorine insecticides) will bind rapidly to submersed macrophytes [20,21], malathion is relatively hydrophilic (Log K OW ¼ 2.3), and it remains unclear how much macrophytes will sorb this insecticide. In the aforementioned experiment by Gao et al [23], the authors found no evidence that malathion was taken up by macrophytes during the first 48 h following exposure. Though they attribute the dissappearance of malathion from the water column after 48 h to sorption by Elodea, the authors only measured malathion's concentration in Elodea on day 8 and thus cannot determine how much of malathion's disappearance from the water column was due to sorption versus other breakdown processes.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…It is generally more difficult to work with organic contaminants because of their molecular diversity, the complexity of analysis, and the constant transformations that they are subject to (Cunningham & Ow, 1996), in addition to the possibility of transforming the pollutants in sub products that are more toxic than the original substance. Some microorganisms (bacteria, micro-algae, and fungi) have also shown a capacity to partially or totally biodegrade the atrazine molecule, resulting in the formation of ammonia (NH 3 ) and carbon dioxide (CO 2 ) (Ueta et al, 1999(Ueta et al, , 2004Gao et al, 2000;Andersona et al, 2002;Lanyi & Dinya, 2003.…”
Section: Introductionmentioning
confidence: 99%